Building infrastructure in the digital age: case study of the Isis Bibliography of History of Science, 2002-2018 - Weldon, Stephen P. (Circumscribere International Journal for the History of Science, 2018)
The IsisCB Explore went online in 2015 as a foundational digital resource for historians of science. Built on the History of Science Society’s 100-year-old Isis Bibliography of the History of Science, this service is meant to lay the groundwork for a digital infrastructure to support historical work in the relatively new digital environment where so much modern scholarship now takes place. In order to create this resource, the director of the project, Stephen Weldon, has learned how to shape traditional historical methods, practices, and resources to fit the new digital paradigm. Computer and networking technologies have been built out of the needs and practices of technologists, natural scientists, and business innovators, all of whom employ it in very specific ways, quite different from the practices of humanistic scholarship, and history in particular. As a result, the digital environment is not especially friendly to historical work or products. As a result, it has taken a great deal of effort to understand and refactor historical data so that it functions well within a digital knowledge ecology, a “knowledge infrastructure,” as Christine Borgman refers to it. This paper describes the difficulties (epistemological, cultural, and economic) that make the creation of tools like the IsisCB Explore service challenging for historians and suggests some ways forward.